Exploiting the defensive sugars of HIV-1 for drug and vaccine design - Scanlan, C; Offer, J; Zitzmann, N; Dwek, R (Nature Research, 2007)
The sustained effort towards developing an antibody vaccine against HIV/AIDS has provided much of our understanding of viral immunology. It is generally accepted that one of the main barriers to antibody neutralization of HIV is the array of protective structural carbohydrates that covers the antigens on the virus's surface. Intriguingly, however, recent findings suggest that these carbohydrates, which have evolved to protect HIV and promote its transmission, are also attractive therapeutic targets.